Intellectual capital efficiency and credit risk in sub-Saharan African banks - Aliyu Ibrahim, Murtala; Md Yusof, Mohd ‘Atef (Opción, 2019)
The purpose of this paper is to study the relationship between intellectual capital (IC) and the credit risk of Sub-Saharan African (SSA) banks. The secondary objective is to test the modified models of Value Added Intellectual Coefficient (VAICTM) method adopted from the study of Vishnu & Kumar Gupta, (2014). Data on 40 SSA banks were collected for empirical testing in this study. The results show no relationship between IC and credit risk. In conclusion, bank size was found to be with significant explanatory powers on credit risk of banks.